When Operating on Dead People Saves Lives: Benefits of Surgical Organ Donor Intensivists - Kristin Long; Cynthia Talley; Rebecca B. Yarrison; Andrew Bernard (Case Reports in Surgery)
Solid organ transplantation has emerged as a life-saving treatment for many patients suffering from end-stage organ failure. Organs have been successfully recovered after a variety of aggressive interventions. We propose that decompressive laparotomy, when clinically indicated, should be considered in the aggressive resuscitation of potential organ donors. A thorough literature review examining aggressive interventions on potential organ donors was conducted after experience with a unique case at this institution. Articles were reviewed for the types of interventions performed as well as the time frame in relation to organ donation. In our case, several ethical issues were raised when considering decompressive laparotomy in a patient pronounced dead by neurologic criteria. We propose that having a surgical intensivist involved in the management of potential donors will further increase the salvage rate, as more invasive resuscitation options are possible.